KULTUR JARINGAN CENDANA (Santalum album L.) MENGGUNAKAN EKSPLAN MATA TUNAS - Toni Herawan; Mohammad Na'iem; Sapto Indrioko; Ari Indrianto (Jurnal Pemuliaan Tanaman Hutan, 2015)
The research aim is to observe tissue culture method for Sandalwood using node explants. The explants were cultured on Murashige and Skoog (MS) medium solidified with agar and supplemented with varies combination of hormones: BAP (benzyl-amino-purine), NAA (napthalene-acetic-acid), IAA (indole-acetic-acid) and Kinetin (furfuril-amino-purine) for shoot induction, multiplication and rooting. The results of study showed that the medium of MS+1 mg/l BAP+0.01 mg/ lNAA provided a good response for shoot induction of Sandalwood clones number A.III.4.14 at around 85%. The medium of MS+0.5 mg/l BAP+0.01 mg/l NAA provided a good response for shoot multiplication of the clones number A.III.4.14 (number of shoot and shoot elongation). The rooting medium of ½MS+20 mg/l IAA+1 mg/l IAA and 0.01 mg/l NAA resulted rooting percentage across the clones at around 37%. The highest survival rate after acclimatization was found at clone number WS6 at around 56%.